2023
DOI: 10.1038/s43018-023-00641-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatic evolution of marine transmissible leukemias in the common cockle, Cerastoderma edule

Alicia L. Bruzos,
Martín Santamarina,
Daniel García-Souto
et al.

Abstract: Transmissible cancers are malignant cell clones that spread among individuals through transfer of living cancer cells. Several such cancers, collectively known as bivalve transmissible neoplasia (BTN), are known to infect and cause leukaemia-like disease in marine bivalve molluscs. This is the case of BTN clones affecting the common cockle, Cerastoderma edule, which inhabits the Atlantic coasts of Europe and north-west Africa. To investigate the origin and evolution of contagious cancers in common cockles, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…While not conclusively demonstrated, we speculate that this increased 5hmC density at these tandems may be linked to distinct chromatin condensation or secondary DNA structures related to chromatin accessibility. However, a remarkable exception was found in CedS4, the major satellite DNA occupying the heterochromatic regions in the healthy lineage (Bruzos et al 2023 ), which was found largely depleted of CpG modifications (Supplementary Table 5 ), as also observed in the methylation and hydroxymethylation desert at the end of Chromosome 11, primarily composed of this satellite (Figs. 1 a, 3 a).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…While not conclusively demonstrated, we speculate that this increased 5hmC density at these tandems may be linked to distinct chromatin condensation or secondary DNA structures related to chromatin accessibility. However, a remarkable exception was found in CedS4, the major satellite DNA occupying the heterochromatic regions in the healthy lineage (Bruzos et al 2023 ), which was found largely depleted of CpG modifications (Supplementary Table 5 ), as also observed in the methylation and hydroxymethylation desert at the end of Chromosome 11, primarily composed of this satellite (Figs. 1 a, 3 a).…”
Section: Resultsmentioning
confidence: 98%
“…Transmissible cancers defy all conventional thinking, as they involve neoplastic cells spreading between individuals beyond their original host (Murchison 2008 ) either through direct contact, as in the canine venereal tumour or the Tasmanian devil facial tumour (Murgia et al 2006 ; Murchison et al 2012 ) or by the absorption of cells freed to the media, as in hemic neoplasia in bivalves (Metzger et al 2015 , 2016 ; Bruzos et al 2023 ; Hart et al 2023 ). Nowadays, this phenomenon extends to, at least, six bivalve species (Metzger et al 2015 ; Hart et al 2023 ), among which, the common cockle, Cerastoderma edule , exhibits two transmissible cancer lineages, differentiated by cytological and genomic features (Bruzos et al 2023 ). These neoplasias are evolutionary relics, accumulating mutations over time (Bruzos et al 2023 ; Hart et al 2023 ) and thus constitute unique models of tumour dynamics, metastasis and evolution (Garcia-Souto et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primers for the MassARRAY genotyping were chosen by their technical feasibility to be combined in two multiplex reactions, taking as reference the cockle genome assembly (Bruzos et al, in press) (Table S1). Briefly, the technique consists of a two‐step reaction: the first involves the PCR amplification of an amplicon which includes the selected SNP (i.e., locus‐specific PCR reaction), and the second a single‐base extension using mass‐modified dideoxynucleotide terminators of an oligonucleotide primer that anneals immediately upstream of the SNP of interest (Ellis & Ong, 2017; Oeth et al, 2009).…”
Section: Methodsmentioning
confidence: 99%